Investigating the relationship between digital citizenship levels and cyberbullying attitudes of university students - Karayol, Metin; Murathan, Talha; Erdoğan, Ramazan; Akarsu, Mehmet; Baş, Muhammet; Norman, Göktuğ (Frontiers in Psychology, 2025)
BackgroundThis study examines the relationship between the levels of digital citizenship and attitudes toward cyberbullying among prospective physical education and sports teachers.MethodsThis quantitative study adopted the relational survey model within its research framework. The sample consists of prospective physical education and sports teachers who studied in the Physical Education and Sports Teaching departments at universities during the 2022–23 academic year. The sample was determined using the convenience sampling method. The sample was administered a personal information form created by the researchers, as well as the Digital Citizenship Scale and the Cyberbullying Attitude Scale.ResultsAccording to the MANOVA results for the Digital Citizenship and Cyberbullying Attitude scales, significant differences were found in the Digital Law, Digital Rights and Responsibilities, Approval and Anxiety subscales based on gender. However, the Pearson correlation analysis revealed no significant relationship between age and the subscales of the Digital Citizenship and Cyberbullying Attitude scales. However, the Pearson correlation analysis of the Digital Citizenship and Cyberbullying Attitude subscales revealed significant positive and negative relationships.ConclusionThe results of the path analysis of the digital citizenship scale and its subscales (identity concealment, enjoyment, approval and anxiety) showed that digital citizenship significantly predicted identity concealment, enjoyment, approval and anxiety.